Aftershocks, groundwater changes and postseismic ground displacements related to pore pressure gradients: Insights from the 2012 Emilia‐Romagna earthquake. Issue 7 (11th July 2017) - Albano, Matteo; Barba, Salvatore; Solaro, Giuseppe; Pepe, Antonio; Bignami, Christian; Moro, Marco; Saroli, Michele; Stramondo, Salvatore
Abstract: During the 2012 Emilia‐Romagna (Italy) seismic sequence, several time‐dependent phenomena occurred, such as changes in the groundwater regime and chemistry, liquefaction, and postseismic ground displacements. Because time‐dependent phenomena require time‐dependent physical mechanisms, we interpreted such events as the result of the poroelastic response of the crust after the main shock. In our study, we performed a two‐dimensional poroelastic numerical analysis calibrated with Cosmo‐SkyMed interferometric data and measured piezometric levels in water wells. The simulation results are consistent with the observed postseismic ground displacement and water level changes. The simulations show that crustal volumetric changes induced by poroelastic relaxation and the afterslip along the main shock fault are both required to reproduce the amplitude (approximately 4 cm) and temporal evolution of the observed postseismic uplift. Poroelastic relaxation also affects the aftershock distribution. In fact, the aftershocks are correlated with the postseismic Coulomb stress evolution. In particular, a considerably higher fraction of aftershocks occurs when the evolving poroelastic Coulomb stress is positive. These findings highlight the need to perform calculations that adequately consider the time‐dependent poroelastic effect when modeling postseismic scenarios, especially for forecasting the temporal and spatial evolution of stresses after a large earthquake. Failing to do so results in an overestimation of the afterslip and an inaccurate definition of stress and strain in the postseismic phase. Key Points: The postseismic phenomena that occurred after the 2012 M w 5.9 northern Italy earthquake depended on the poroelastic response of the crust Poroelastic relaxation is equally important as the afterslip in terms of the aftershock distribution DInSAR ground deformation data and in‐well water level changes were used to successfully calibrate the poroelastic numerical model